Stakeholder value appropriation: The case of labor in the worldwide mining industry - Ramírez, Cristian; Tarziján, Jorge (Strategic Management Journal, 2018)
[Research Summary: We evaluate how the value appropriated by employees varies in response to an exogenous shock to the price of the firm's product and how this variation depends on institutional and ownership structures. Institutional and ownership structures that favor employees can influence firms' location decisions and shareholders' incentives to invest. Using data from the main copper mines in the world, we show that the value appropriated by employees rises in response to an exogenous increase in the price of minerals. Our results indicate that the magnitude of the increment in the value captured by employees is larger in stated-owned companies, when labor regulations promote productivity-based payments, when wages are determined through a centralized bargaining process, and when regulations associated with hiring and firing are more flexible. Managerial Summary: We show how labor regulations and state ownership affect the value appropriated by employees when there are exogenous changes in the price of the firm's products. Since the value generated by a firm is distributed among different stakeholders, a higher appropriation of value by employees results in lower appropriation by another party. Therefore, by changing the distribution of value, managerial decisions about location and entry could be affected. For instance, shareholders of firms with positive future expectations about the prices of their products might prefer to enter markets in which salary negotiations are not centralized or where partnership with the local government is not mandatory. Overall, our analysis calls for the consideration of the external environment when evaluating value appropriation by different types of stakeholders.]